Probiotic Lactobacillus johnsonii BS15 Improves Blood Parameters Related to Immunity in Broilers Experimentally Infected with Subclinical Necrotic Enteritis - Wang, Hesong; Ni, Xueqin; Qing, Xiaodan; Liu, Lei; Xin, Jinge; Luo, Min; Khalique, Abdul; Dan, Yan; Pan, Kangcheng; Jing, Bo; Zeng, Dong (Frontiers in Microbiology, 2018)
The probiotic strain Lactobacillus johnsonii BS15 could exert beneficial effects on growth performance, lipid metabolism, and intestinal microflora in healthy broilers and those afflicted with subclinical necrotic enteritis (SNE). In particular, BS15 prevents SNE by enhancing intestinal immunity. To further understand the immune regulatory mechanism of BS15, we evaluated its effects on the overall immunity of broilers by determining blood parameters in healthy and SNE broilers. In this study, two experiments were conducted. Experiment 1 involved a 42-day experimental period and used 450 1-day-old male chicks. The chicks were randomly divided into three groups and fed with a basal diet with or without 1 × 105 or 106 colony-forming units (cfu) BS15/g as feed. Experiment 2 involved a 28-day experimental period and used 180 1-day-old male chicks. The chicks were randomly allotted into three groups and given with or without 1 × 106 cfu BS15/g BS15 as feed. SNE infection was treated in all broilers, except in those in the normal diet group. Antioxidant abilities, immunoglobulins, and cytokines in the serum were assessed. T-lymphocyte subsets in peripheral blood were also determined. The first experiment demonstrated that BS15 enhanced the antioxidant abilities; the serum levels of immunoglobulins, interleukin-2, and interferon-gamma; and CD3+CD4+ T-lymphocyte percentage in peripheral blood on day 21. However, limited significant changes were observed on day 42. The second experiment revealed that BS15 supplementation positively influenced the antioxidant abilities and increased the serum levels of immunoglobulins and cytokines that were affected by SNE. BS15 also positively affected T-lymphocyte subsets in peripheral blood during SNE infection. These findings suggest that BS15 supplementation may prevent SNE in broilers by improving blood parameters related to immunity and enhancing intestinal immunity. Furthermore, BS15 supplementation can improve blood parameters in healthy broilers, especially at the starter phase.